Literature Review: Implementasi Sistem Informasi Kesehatan Puskesmas di Berbagai Daerah - Zahra Arwananing Tyas; Wira Nata Negara (JTIS: Journal of Technopreneurship and Information System, 2022)
Health Information System (SIK) is a set of arrangements that include interrelated data, information, indicators, procedures, tools, technology and human resources. The purpose of this study was to explore and describe in-depth information regarding the implementation of the Health Information System (SIK) in puskesmas in Indonesia, in terms of effectiveness, efficiency, and transparency, in managing data and information. This type of research is a qualitative research with a literature study approach. The research subjects consisted of 4 journals. The results of the study showed that the implementation of the Puskesmas SIK was viewed from the aspect of effectiveness: there were still deviations, in the form of inconsistent data or errors in health data and information in data and information management. The implementation of the Puskesmas SIK is viewed from the aspect of efficiency: data processing using a computerized system; maintenance that is not carried out regularly every year; consistency in data transmission has not been consistent. The implementation of the Puskesmas SIK is viewed from the aspect of transparency: information systems in various regions in Indonesia have shown openness with reporting. This means that the implementation of SIK puskesmas in various regions in Indonesia in terms of effectiveness, efficiency, and transparency in data and information management, is generally not good so it still needs improvement.